PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN SEKTOR PERBANKAN SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kurniawati, Desi (Jurnal Ilmiah Publika, 2023)
This research aims to analyze the influence of Intellectual Capital (VAHU, STVA and VACA) as an independent variable on Financial Performance as measured by Net Profit Margin (NPM). This research uses a sample of six Islamic banks listed on the Indonesian Stock Exchange for the 2011-2022 period. The sampling method used was the purposive sampling method. The empirical results of this research show that partially, the results of the t test explain that the influence of the Intellectual Capital variables (VAHU, STVA and VACA) on Financial Performance, only the STVA variable has a significant negative effect, while the other two variables (VAHU and VACA) do not have significant influence on financial performance.